The catastrophic antiphospholipid syndrome and the microangiopathic antiphospholipid syndrome - Asherson, Ronald (Henry Stewart Talks, 2007)
Description of the antiphospholipid syndrome (APS), Primary, secondary and intermediate syndromes, Thrombotic and non-thrombotic manifestations of the APS, Beta 2 glycoprotein 1, Relationship of APS to CAPS, Clinical manifestations of CAPS, Triggering factors, Pathogenesis, Microangiopathic antiphospholipid syndromes
Reviewed at 2017/05/17